A Ramp versus Step Transition to Constant Work Rate Exercise Decreases Steady-State Oxygen Uptake - Marinari, Gabriele; Iannetta, Danilo; Holash, Robert John; Trama, Robin; Faricier, Robin; Zagatto, Alessandro M. [UNESP]; Keir, Daniel A.; Murias, Juan M. (Wolters Kluwer, 2024)
Within the initial minutes of square-wave exercise transitions above the moderate-intensity domain, the reliance on the anaerobic energy sources may induce some levels of metabolic instability; however, no study has attempted to limit metabolic instability at exercise onset by manipulating the exercise transition phase to a target work rate (WR). Purpose This study aimed to investigate whether a ramp-to-constant WR (rCWR) transition compared with a square-wave-to-constant WR (CWR) transition within the heavy-intensity domain can reduce metabolic instability and decrease the oxygen cost of exercise. Methods Fourteen individuals performed (i) a ramp-incremental test to task failure, (ii) a 21-min CWR within the heavy-intensity domain, and (iii) an rCWR to the same WR. Oxygen uptake (VO2), lactate concentration ([La-]), and muscle oxygen saturation (SmO2) were measured. VO2 and VO2 gain (VO2-G) during the first 10-min steady-state VO2 were analyzed. [La-] before, at, and after steady-state VO2 and SmO2 during the entire 21-min steady-state exercise were also examined. Results VO2 and VO2-G during rCWR (2.49 ± 0.58 L·min-1 and 10.7 ± 0.2 mL·min-1·W-1, respectively) were lower (P < 0.001) than CWR (2.57 ± 0.60 L·min-1 and 11.3 ± 0.2 mL·min-1·W-1, respectively). [La-] before and at steady-state VO2 during the rCWR condition (1.94 ± 0.60 and 3.52 ± 1.19 mM, respectively) was lower than the CWR condition (3.05 ± 0.82 and 4.15 ± 1.25 mM, respectively) (P < 0.001). [La-] dynamics after steady-state VO2 were unstable for the rCWR (P = 0.011). SmO2 was unstable within the CWR condition from minutes 4 to 13 (P < 0.05). Conclusions The metabolic disruption caused by the initial minutes of square-wave exercise transitions is a primary contributor to metabolic instability, leading to an increased VO2-G compared with the rCWR condition approach. The reduced early reliance on anaerobic energy sources during the rCWR condition may be responsible for the lower VO2-G.
Keywords: ANAEROBIC ENERGY SOURCES; MUSCLE BIOENERGETICS; MUSCLE OXYGEN SATURATION; OXIDATIVE PHOSPHORYLATION; OXYGEN COST; OXYGEN UPTAKE SLOW COMPONENT